Topical Delivery of Carvedilol Loaded Nano-Transfersomes for Skin Cancer Chemoprevention - Mengbing Chen; Md Abdullah Shamim; Ayaz Shahid; Steven Yeung; Bradley T. Andresen; Jeffrey Wang; Vijaykumar Nekkanti; Frank L. Meyskens; Kristen M. Kelly; Ying Huang (MDPI AG, 2020)
The β-blocker carvedilol has been shown to prevent skin carcinogenesis in vitro and in vivo. Since systemic absorption of the β-blocker may cause cardiovascular disturbance, we developed a carvedilol loaded transfersome for skin-targeted delivery. Transfersomes were prepared using phospholipids and surfactants at various ratios and characterized. One formulation (F18) selected for further analysis was composed of carvedilol, soy phosphatidylcholine, and Tween-80 at a ratio of 1:3:0.5, which had a particle size of 115.6 ± 8.7 nm, a zeta potential of 11.34 ± 0.67 mV, and an encapsulation efficiency of 93.7 ± 5.1%. F18 inhibited EGF-induced neoplastic transformation of mouse epidermal JB6 P+ cells at non-toxic concentrations, while only high concentrations induced cytotoxicity in JB6 P+ and human keratinocytes HaCaT. Compared to the free drug, F18 released through the dialysis membrane and permeated through the porcine ear skin at a slower rate, but similarly depositing the drug in the epidermis and dermis of the skin. Consistently, surface application of F18 on reconstructed full-thickness human skin showed slower drug permeation, while it suppressed ultraviolet-induced DNA damage, inflammatory gene expression, and apoptosis. These data indicate that transfersome is a promising topical delivery system of carvedilol for preventing ultraviolet-induced skin damage and carcinogenesis.